Phage Display-Derived Peptides and Antibodies for Bacterial Infectious Diseases Therapy and Diagnosis - Hui Zhao; Dan Nie; Yue Hu; Zhou Chen; Zheng Hou; Mingkai Li; Xiaoyan Xue (Molecules, 2023)
The emergence of antibiotic-resistant-bacteria is a serious public health threat, which prompts us to speed up the discovery of novel antibacterial agents. Phage display technology has great potential to screen peptides or antibodies with high binding capacities for a wide range of targets. This property is significant in the rapid search for new antibacterial agents for the control of bacterial resistance. In this paper, we not only summarized the recent progress of phage display for the discovery of novel therapeutic agents, identification of action sites of bacterial target proteins, and rapid detection of different pathogens, but also discussed several problems of this technology that must be solved. Breakthrough in these problems may further promote the development and application of phage display technology in the biomedical field in the future.